Epigenetic Regulation of Signalling Pathways in Pancreatic Cancer - Faleiro, Inês Correia da Silva Pires (2018)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017